Analisis Pengaruh Stres Kerja dalam Memediasi Hubungan Antara Politik Organisasional dengan Perilaku Agresif (Studi Kasus pada RS PKU Muhammadiyah dan DKT Di Yogyakarta) - Yuni Siswanti (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2006)
This research aim to test the impact of organizational politics to job distress and aggressive behavior, and research mediation effect job distress of relation of organizational politics and aggressive behavior. The data were collected from two hospitals, are PKU and DKT in Jogjakarta from nurses. Total respondent were 86 peoples. Regression and hierarchical regression Analysis (HRA) analyzed the data. The interesting result that organizational politics was direct effected to job distress, but wasn’t direct effected to aggressive behavior. The research has succeeded establish that job distress as mediator variable in the relation of organizational politics and aggressive behavior.Keywords: organizational behavior, job distress, aggressive behavior